Autologous Fascia Lata Graft in Scleromalacia Perforans: A Rare Case: Poster Presentation - Case Report - Resident - ANCI WINAS; Petty Purwanita; Anang Tribowo (Majalah Oftalmologi Indonesia, 2023)
Introduction : Scleromalacia perforans, also called anterior necrotizing scleritis without inflammation, is a rare disease with an initial lesion of yellow or greyish nodules that gradually develop into scleral necrosis with perforation and exposure of uvea. It typically occurs in elderly women. Surgical therapy to close the defect may be performed with the sclera, dermis, fascia lata, periosteum, aortic tissue, cartilage, and eventually amniotic membrane as grafts. Case Illustration : A 59-year-old woman presented with complaint of greyish discoloration of the sclera on the right eye since one years ago. The patient denied the history of arthritis, autoimmune diseases, and other systemic diseases. The patient claimed to have had pterygium surgery ten years ago. Visual acuity was 6/9 with an of IOP 13.1 mmHg. Slit lamp examination revealed thinning of the medial sclera. Posterior segment was within normal limits. Serum antibody screening obtained normal results. The patient was diagnosed with scleromalacia perforans and underwent autologous fascia lata graft surgery. Two weeks postoperatively, scleral of the fascia lata graft gave good results. Discussion : Scleromalacia perforans is diagnosed based on anamnesis and ophthalmological examination. A history of pterygium surgery is suspected as the trigger for scleral thinning. Surgical therapy was performed to maintain the integrity of the eyeball and prevent further thinning of the sclera. Autologous fascia lata graft is chosen because it is readily available, easy to perform, and has a low rejection rate. Conclusion : Autologous fascia lata graft is a surgery that provides good prognosis in scleromalacia perforans.